(untitled) - Cooper, Geoffrey M. (Washington, D.C., 1997)
The third edition of this text/CD-ROM for an introductory cell biology course contains expanded material on areas such as genome sequencing, DNA microarrays, and stem cells. Coverage includes the flow of genetic information, cell structure and function, and cell regulation. The CD-ROM contains tutorials on basic topics, animations of key concepts and processes, video microscopy sequences, and spoken pronunciations.
Keywords: Cytology,Molecular biology,Tế bào học,Sinh học phân tử